General practitioners in German metropolitan areas – distribution patterns and their relationship with area level measures of the socioeconomic status. Issue 1 (December 2016) - Bauer, Jan; Brueggmann, Doerthe; Ohlendorf, Daniela; Groneberg, David
Abstract Background Geographical variation of the general practitioner (GP) workforce is known between rural and urban areas. However, data about the variation between and within urban areas are lacking. Method We analyzed distribution patterns of GP full time equivalents (FTE) in German cities with a population size of more than 500, 000. We correlated their distribution with area measures of social deprivation in order to analyze preferences within neighborhood characteristics. For this purpose, we developed two area measures of deprivation: Geodemographic Index (GDI) and Cultureeconomic Index (CEI). Results In totaln = 9034.75 FTE were included inn = 14 cities withn = 171 districts. FTE were distributed equally on inter-city level (mean: 6.49; range: 5.12–7.20; SD: 0.51). However, on intra-city level, GP distribution was skewed (mean: 6.54; range: 1.80–43.98; SD: 3.62). Distribution patterns of FTE per 10^4 residents were significantly correlated with GDI (r = −0.49;p < 0.001) and CEI (r = −0.22;p = 0.005). Therefore, location choices of GPs were mainly positively correlated with 1) central location (r = −0.50;p < 0.001), 2) small household size of population (r = −0.50;p < 0.001) and 3) population density (r = 0.35;p < 0.001). Conclusion Intra-city distribution of GPs was skewed, which could affect the equality of access for the urban population. Furthermore, health services planners should be aware of GP location preferences. This could be helpful to better understand and plan delivery of health services. Within this process the presented Geodemographic Index (GDI) could be of use.